A Literature Review on Takaful’s Evolution with Blockchain: Challenges and Opportunities - Marrisa Andinarianti; Andriani Samsuri (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2026)
This literature review explores the evolution of Takaful, an Islamic insurance model based on mutual cooperation and shared responsibility, and its integration with blockchain technology. Takaful has experienced significant growth over the past few decades, driven by the increasing demand for Sharia-compliant financial solutions. However, the industry faces challenges such as lack of transparency, operational inefficiencies, and high administrative costs. Blockchain technology, with its characteristics of immutability, transparency, and decentralization, presents opportunities to address these challenges by enhancing operational efficiency, improving transparency, and reducing fraud. This review synthesizes existing research on the intersection of Takaful and blockchain, highlighting the historical roots of Takaful, the impact of blockchain on its operations, and the regulatory, technical, and socio-cultural challenges that accompany this integration. The findings underscore the potential of blockchain to revolutionize the Takaful industry while emphasizing the need for further research to navigate the complexities of implementation and ensure compliance with Islamic principles.